Simulating an electrochemical interface using charge dynamics - Guymon, C.G.; Rowley, R.L.; Harb, J.N.; Wheeler, D.R. (Condensed Matter Physics, 2005)
We present a simple classical method for treating charge mobility in metals
adjacent to liquid solutions. The method, known as electrode charge
dynamics, effectively bridges the computational gap between ab initio calculations
on small metal clusters and large-scale simulations of metal surfaces
with arbitrary geometry. We have obtained model parameters for a
copper (111) metal surface using high-level quantum-mechanical calculations
on a 10-atom copper cluster. We validated the model against the
classical image-charge result and ab initio results on an 18-atom copper
cluster. The model is used in molecular dynamics simulations to predict
the structure of the fluid interface for neat water and for aqueous NaCl solution.
We find that water is organized into a two-dimensional ice-like layer
on the surface and that both Na⁺ and Cl⁻ are strongly bound to the copper.
When charging the metal electrode, most of the electrolyte response
occurs in the diffuse part of the double layer Ми представляємо простий класичний метод для трактування зарядової мобільності у металах, які межують з рідкими розчинами.
Метод, відомий як електродна зарядова динаміка, ефективно
заповнює прогалину між ab initio розрахунками на малих металічних
кластерах і велико-масштабними симуляціями металічних поверхонь з довільною геометрією. Ми отримали модельні параметри для
металічної (111) поверхні міді, використовуючи квантово-механічні
розрахунки високого порядку на 10-атомному мідному кластері.
Модель була перевірена шляхом порівняння з класичними результатами по методу відображень, а також з ab initio результатами для
18-атомного мідного кластера. Модель використана в молекулярно динамічних розрахунках для структури флюїдної поверхні чистої
води і водного розчину NaCl. Ми побачили, що вода організовується
у двовимірний льодоподібний шар на поверхні і що обидва, Na⁺ i
Cl⁻, іони є сильно прив’язані до міді. Коли металічний електрод заряджати, то основна реакція електроліту проявляється у дифузивній
частині подвійного шару.